Valuable components of bambangan fruit (Mangifera pajang) and its co-products: a review - Akanda, Md Jahurul Haque; Sarker, Md. Zaidul Islam; Beh, Leykey; Sharifuddin, Md Shaarani; Siddiquee, Shafiquzzaman; Mamat, Hasmadi; Sahena, Ferdosh; Abdul Hamid, Mansoor; Lee, J. S.; Jinap, Selamat (Elsevier BV, 2019)
Fruits are important food commodities that can be consumed either raw or processed and are valued for their taste, nutrients, and healthy compounds. Mangifera pajang Kosterm (bambangan) is an underutilized fruit found in Malaysia (Sabah and Sarawak), Brunei, and Indonesia (Kalimantan). It is highly fibrous and juicy with an aromatic flavour and strong smell. In recent years, bambangan fruit has been gaining more attention due to its high fibre, carotenoid content, antioxidant properties, phytochemicals, and medicinal usages. Therefore, the production, trade, and consumption of bambangan fruit could be increased significantly, both domestically and internationally, because of its nutritional value. The identification and quantification of bioactive compounds in bambangan fruit has led to considerable interest among scientists. Bambangan fruit and its waste, especially its seeds and peels, are considered cheap sources of valuable food and are considered nutraceutical ingredients that could be used to prevent various diseases. The use of bambangan fruit waste co-products for the production of bioactive components is an important step towards sustainable development. This is an updated report on the nutritional composition and health-promoting phytochemicals of bambangan fruit and its co-products that explores their potential utilization. This review reveals that bambangan fruit and its co-products could be used as ingredients of dietary fibre powder or could be incorporated into food products (biscuits and macaroni) to enhance their nutraceutical properties